Pengaruh Perbandingan Tepung Ampas Kelapa dengan Tepung Terigu Terhadap Mutu Brownies - Hasan, Irma (Universitas Gorontalo, 2018)
waste oil is the result addition to the manufacture of coconut milk, coconut meat processed into coconut oil of processing way wet be procured byproduct waste oil. until now utilization is limited to feed and partly be Tempe bongkrek for food. based on the analysis of waste oil still high-value when used as the flour for food ingredients high protein. this study aims untukmengetahui the influence of waste oil terhada water content, karbohidat and organoleptic (color, taste, aroma and texture) brownies.manfaat this study is to provide information on the broad about making brownies with the addition of flour waste oil and can be applied to the product food economic value because flour waste oil has a high content protein, low fat, and gluten-free. this study using the method is composed of creation phase flour waste oil and making process brownies. engineering data processing using the design of randomized complete (RAL), which consists of three treatment and three replicates. brownies the generated then in the test of the content of water content, level of carbohydrate and test organoleptic (color, taste, aroma and texture). of research results brownies of wheat flour and flour dregs coconut obtained highest average that is in the treatment with a comparison of wheat flour 55 grams and flour dregs coconut 45 grams with water content 39,0%, comparison of wheat flour 75 grams and flour dregs coconut 25 grams grading carbohydrates 45,8% and test organoleptic each preferred by panelists terms of aroma, color, taste.Â Keywords : Sago Flour, All Purpose Flour, Bread Flour, The Addition Of Sago